Psychosocial Construction Work Environment and Wellbeing in the Viability of Indigenous Construction Firms - Olubimbola Oladimeji (Journal of Engineering, Project, and Production Management, 2020)
The strategic role of indigenous construction firms (ICFs) in the development of the construction industry better construction output and infrastructural development in developing countries cannot be overemphasized. These goals may not be achieved if firms’ psychosocial construction work environment and wellbeing (PCEW) are not appraised. To this end, this study identified and assessed factors relating to PCEW in the 37 factors influencing the viability and performance of construction firms obtained from the extant literature. A sample size of 65 staff of 31 ICFs out of a total survey of 177 staff of 59 ICFs that were awarded building contracts in selected institutions in Nigeria was accessed for this study. Respondents rated each factor on a five-point Likert scale of importance and mean scores were used to rank the factors after identifying factors that are related to ICFs’ PCEW. The study identifies 14 PCEW related factors out of the 37 factors influencing the viability of ICFs and six of the top ten very important factors influencing ICFs’ viability having high factor loading are PCEW related. The factors are quality of construction work and services, availability of skilled labour, employee satisfaction, and availability of artisans and craftsmen. Steady emphasis on factors influencing PCEW of construction workers amidst various factors influencing ICFs’ viability is necessary for a healthier construction work environment and wellbeing.